Non-traumatic esophageal perforation: A case report on Boerhaave’s syndrome (Indian Journal of Case Reports, 2024)
Boerhaave’s syndrome is a potentially fatal condition characterized by spontaneous perforation of a previously healthy esophagus, due to severe vomiting or straining. It often presents with non-specific symptoms such as fever, pain, and vomiting and hence may go undiagnosed. The Makler’s triad, consisting of vomiting, chest pain, and subcutaneous emphysema, may be seen in only 50% of cases. Delayed diagnosis may result in complications such as sepsis, mediastinitis, pneumothorax, and multi-organ dysfunction. In general, patients presenting later than 48 h are conservatively managed with esophageal stenting. Surgical repair is usually reserved for those patients who present within 24 h, or are managed conservatively and develop complications. Mortality rises from 0% if treated within 24 h to about 29% if delayed more than 48 h. We present a case of Boerhaave’s syndrome in a 35-year-old male who presented with spontaneous respiratory distress and hemodynamic instability, about 36 h after the onset of vigorous vomiting. The case was managed initially with endoscopic insertion of a self-expanding metallic stent, followed later by surgical closure of the esophageal perforation. The patient, however, developed post-operative septic complications and died after a week.